2019
DOI: 10.1002/cbin.11209
|View full text |Cite
|
Sign up to set email alerts
|

EGFR signaling pathway occupies an important position in cancer‐related downstream signaling pathways of Pyk2

Abstract: Proline‐rich tyrosine kinase 2 (Pyk2) is a member of focal adhesion kinase (FAK) non‐receptor tyrosine kinase family and has been found to promote cancer cell survival, proliferation, migration, invasion, and metastasis. Pyk2 takes part in different carcinogenic signaling pathways to promote cancer progression, including epidermal growth factor receptor (EGFR) signaling pathway. EGFR signaling pathway is a traditional carcinogenic signaling pathway, which plays a critical role in tumorigenesis and tumor progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Our findings demonstrated that pepsin, in vitro, at slightly acidic pH of 6.0 and in particular at neutral pH of 7.0 preserves cell survival and induces activation of specific oncogenic markers clinically associated with HNSCC [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 51 , 53 ]. Despite the possible pepsin-related stress toxicity and damage in cancer hypopharyngeal cells at either pH 7.4 or pH 7.0 [ 21 , 24 ], using our model, we provide evidence of the oncogenic effect of pepsin in normal HCs at pH 7.0 or 6.0, in line with other observations by Johnston’s team [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our findings demonstrated that pepsin, in vitro, at slightly acidic pH of 6.0 and in particular at neutral pH of 7.0 preserves cell survival and induces activation of specific oncogenic markers clinically associated with HNSCC [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 51 , 53 ]. Despite the possible pepsin-related stress toxicity and damage in cancer hypopharyngeal cells at either pH 7.4 or pH 7.0 [ 21 , 24 ], using our model, we provide evidence of the oncogenic effect of pepsin in normal HCs at pH 7.0 or 6.0, in line with other observations by Johnston’s team [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 77%
“…Elucidating the mechanism of the effect of pepsin on HCs, we showed the abundant activation of EGFR, which was documented by a significant overexpression of phospho-EGFR and EGFR mRNAs, accompanied by activation of two more oncogenic factors, NF- κ B and STAT3, and a significant upregulation of genes linked to related oncogenic signaling pathways, such as EGFR/AKT1/mTOR , TNF-α/RELA(p65)/BCL2 , STAT3 and cancer-related cytokines, IL6 and IL1β . It is known that EGFR activation can exert an oncogenic effect by activating downstream oncogenic pathways, such as AKT/mTOR, STAT3 and NF- κ B [ 39 , 40 , 41 , 42 , 44 ], strongly supporting the role EGFR as a key molecule of the pepsin-induced tumorigenic effect on the hypopharynx in a less acidic environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When EGFR was activated, proliferation, differentiation, transformation, angiogenesis, migration, and survival of cancer cells were induced [ 9 ]. Phosphorylation of EGFR activates the downstream components including ERK, PI3K/Akt, and STAT signaling pathways [ 10 ], which play a crucial role in cancer metastasis [ 11 ]. In addition, several studies reported that the EGFR signaling pathway also regulated MMP expression [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%